Strengthening the Management Capacity of Joint Business Groups (KUBE) in Utilizing Raw Corn Materials as Products in Barakati Village - Ivan Rahmat Santoso; Ismet Sulila (Jurnal Pengabdian Pada Masyarakat, 2023)
The level of marketing of raw corn materials is still relatively low. This is because corn farmers only sell their produce in the form of raw corn directly to traditional markets. This program aims to strengthen the management capacity of community groups in increasing the added value of raw corn materials as a product variety. In addition, this program also aims to absorb labor and increase people's income through increased creativity and local innovation that can be made into regional specialties. The method used in this program is the technical guidance method. The results of this service program include increasing understanding of community groups processing corn into products of economic value as an effort to improve welfare, fostering group independence in processing corn into various healthy and hygienic snack products, and increasing the income of target community groups as a result of selling snack products.